Revision of the Neotropical moth genus Ptychotrichos Schaus (Lepidoptera, Erebidae, Arctiinae, Arctiini, Ctenuchina) - Pinheiro, Lívia R.; Duarte, Marcelo (Zootaxa, 2017)
Ptychotrichos Schaus, 1894 is revised and redescribed based on external and genitalia characters. The genus is now characterized by the following autapomorphic characters: forewing more than twice as long as hindwing, hairbrush on dorsal surface of inner margin of hindwing, vinculum sigmoid, uncus bilobed, and valva with a proximal finger-like projection. Ptychotrichos is comprised of two species, P. zeus Schaus, 1894 (type-species) and P. elongata Schaus, 1905, which differ from each other in fore- and hindwing patterns, coloration of abdominal tergites and male and female genitalia. Both species of Ptychotrichos are redescribed and illustrated, and maps of their geographical distribution are provided, with a discussion on the unusual distribution of P. zeus. A new combination for Ptychotrichos [sic] fenestrifer Zerny, 1931 is also proposed: Heliura fenestrifer comb. nov.